2018
DOI: 10.3390/resources7030047
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm of Management Decision-Making Regarding the Feasibility of Investing in Geological Studies of Forecasted Hydrocarbon Resources

Abstract: Currently, under the conditions of increasing depletion of hydrocarbon reserves in Russia, it is necessary to consider the resource potential of poorly-researched oil and gas objects as a factor for ensuring the sustainable development of the oil and gas complex, in the context of the concept formation of rational subsoil utilization and a circular economy. The methodology of this study is based on a clear sequence of geological and economic studies of poorly-researched oil and gas objects, including four stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
(24 reference statements)
0
12
0
3
Order By: Relevance
“…Thus, it is necessary to determine the vector = ( , , … , , … , ) − -the volume of requirements imposed by agents on the distributed resource [68][69][70][71][72]. The evaluation of the vector x is one of the most difficult and contested quantities in the problem.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it is necessary to determine the vector = ( , , … , , … , ) − -the volume of requirements imposed by agents on the distributed resource [68][69][70][71][72]. The evaluation of the vector x is one of the most difficult and contested quantities in the problem.…”
Section: Resultsmentioning
confidence: 99%
“…Standard methods, such as the scenario approach (Cherepovitsyn et al, 2018), are widely used in investment design and in assessing the value of the object, using the income approach. In the works (Ozerov, 2007;Pupentsova & Livintsova, 2018), it was shown that, when choosing the best and most effective use of the object, uncertainty in the source data and in the predictions of their changes can lead to an erroneous choice.…”
Section: Methodsmentioning
confidence: 99%
“…Для России вопросы повышения эффективности геологоразведки стоят крайне остро, в том числе и на этапах промышленного освоения месторождения, где важна доразведка пластов и получение возможного прироста запасов углеводородов [57]. Арктические НГП могут компенсировать снижение запасов легкоизвлекаемых углеводородов в старопромысловых регионах, но необходимо отметить еще низкий уровень разведанности некоторых территорий арктической зоны хозяйствования [58].…”
Section: динамика накопленного числа цитирований и публикаций по годамunclassified